Proposed Marketing Strategy of Cookies n Chill Based on New Normal Baked Goods Business Ecosystem (The Indonesian Journal of Business Administration, 2021)
Cookies n Chill is a local culinary brand that focuses on American-style cookie, officially launched on January 1st, 2020. Cookies n Chill products are hoped can share the joy to anyone who enjoys it. The company experienced sales decreased in April 2020. Consumer behavior has changed due to the COVID-19 pandemic that began to spread in Indonesia. The purpose of this research is to determine the right business strategy for the current situation and find out how to grow business transactions and the volume of customer interactions to survive at critical times.This study uses internal and external analysis to determine the company's condition and determine the source of the problems. For internal analysis, this study uses Existing Business Model Canvas. For the external analysis, the company uses Customer Analysis to determine further customer wants and needs. After knowing its internal and external conditions, the marketing variable was chosen as the most crucial problem. It expected to help solve other Cookies n Chill problems.With Proposed Marketing Strategy (Marketing Mix 7P), recommendations that can be given in this study are adding a new menu for a niche market; healthy cookie lines. In the future, it is possible to add new variants according to market demand. Social media optimization, such as Instagram and Twitter, is also needed for promotional purposes. Food blogger recommendations and Facebook ads are also Cookies n Chill marketing strategies. Business expansions strategies are consignment partnership with coffee shops and registering as a tenant in food festivals after the COVID-19 pandemic has ended. At the same time, additional employees are needed after business transactions have improved. Keywords: Marketing, Marketing Mix, Baked Goods, Covid-19, Business Ecosystem